Способи покращення параметрів модифікованого генератора Голлманна - Максимович, Володимир; Костів, Юрій (Видавництво Національного університету «Львівська політехніка», 2009)
Abstract Research of the modified generator of Gollmanna. Increase period repetition of pseudorandom numbers generators (PRNG). Research was conducted with the help of the created simulation model.
Keywords: generator; pseudorendom numbers; M- sequences; simulation model; generator of Gollmanna; генератор псевдовипадкових чисел; генератор Голлманна